Factores de riesgo que influyen en la conducta suicida de los adolescentes atendidos en el área de emergencia del Hospital Martin Icaza, noviembre 2023- abril 2024 - Angamarca Verdezoto, Liseth Estefanía (2024)
Suicidal behavior, considered a form of violence directed towards oneself, has a global mortality rate of 16 per 100,000 people, showing an increase during adolescence. The general objective of this study was to determine the risk factors that influence the suicidal behavior of adolescents treated in the emergency area of the Martin Icaza Hospital, November 2023-April 2024, whose methodology used a type of applied, field, research. descriptive and longitudinal, with a deductive, historical-logical research method, analysis method and qualitative-quantitative modality. The total sample is made up of 50 adolescents treated in the emergency area, where the questionnaire used is carried out on the study population. The results obtained in this research highlight that the male gender is the most predominant with 60%, age group from 15 to 19 years 76%, single marital status with 92%, rural residential area 62%, type of cement housing 40%, 70% had basic services, high school education with 46%, in addition to perceiving low self-esteem with 80%, income of 300 dollars, represented by 34%, they had no family history of suicidal behavior, 50% live with their biological parents, 70% do not have a family nucleus, physical abuse is the most frequent with 34%. Depression was the most significant factor, they did not present any type of personality disorder diagnosis, 42% solved their problems on their own. The most frequent method of self-harm is with pills with 36%, patients made self-harm attempts every 6 months with 42% and 56% received therapeutic treatment. As a conclusion of the research work, it is determined that risk factors and demographic characteristics influence the suicidal behavior of adolescents who attend the hospital establishment.